Language Dromology: A New Abbreviation Phenomenon in Twitter Messages - Viono, Tono; Yanti AD, Zully Hijah; Busri, Hasan; The, Hery Yanto (Universitas Muhammadiyah Malang, 2023)
In this era, technological developments increasingly show complex influences on cultural discourse due to the tremendous speed of information production. Language as a product of culture is essential as a reflective tool for every social practice. Using abbreviations on social media, Twitter shows a tendency for language acceleration. This study aims to explore some of the emergences of abbreviation forms and patterns on Twitter social media, then explore the function of meaning generated through a dromological perspective. The research method used is descriptive qualitative. Data was collected through note-taking techniques in Twitter messages from 1 – 14 March 2023 in the Malang City region. The findings of abbreviations in social media Twitter consist of 28 alphabetisms, 17 acronyms, and 18 clippings. Through a dromological perspective, it was found that the communication model through abbreviation experiences hyper-reality, shallow meaning, banality, wear and tear, and identity fragmentation. The number of uses of abbreviated words on social media cannot be a benchmark as a new lexeme in KBBI, and it is recommended that a comprehensive critical verification will become a counter-model to this kind of speed logic.